(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Austin is one of the most important jurists who have offered something exceptional to the world and to the subject of Jurisprudence. From all the four schools, quite a lot more attention and importance is given to the Analytical School of Jurisprudence. The historical development of the subject of jurisprudence is incomplete without the analytical thinking and positivism theories propounded by various jurists who supported and added to the views of Austin. The importance of the theory is so much that the concept is relevant even today. Ages have passed and the governance has changed from dictatorship to authoritative governments to democratic and a republican form of Government. The concept is even today relevant and the correct application of the theory would definitely help Jurists and modern day government forerunners to develop an even better governance for all. The Author through this paper stresses on the importance of the analytical thoughts propounded by Austin and proposes them in a way to explain all the theoretical aspects first and then goes to explain how the same is relevant in today’s constitutional principles. The concept of positivism is incomplete without the theory of sovereignty and thus, the same is covered in depth.